Psychosocial Determinants of Weight Loss Among Young Adults With Overweight and Obesity: HOW DOES DRIVE FOR THINNESS AFFECT WEIGHT LOSS?. Issue 2 (March 2018) - Falck, Ryan S.; Best, John R.; Drenowatz, Clemens; Hand, Gregory A.; Shook, Robin P.; Lavie, Carl J.; Blair, Steven N.
Abstract : Purpose: The ardent wish to lose weight, drive for thinness (DT), might be 1 psychosocial contributor to weight loss (WL) in adults with overweight and obesity. In examining DT as a predictor of WL, it is important to determine whether its predictive value is equal in males and females and whether it exerts its effects primarily through changes in diet or physical activity (PA). Methods: Two-hundred three men and women with overweight and obesity (body mass index >25 kg/m 2 ; aged 21-35 years; 47% female) participated in this 12-month observational study. DT score and demographic information were collected at baseline. Participants were measured at quarterly intervals for objectively measured PA, energy intake, and anthropometrics. Linear mixed regression analyses determined whether DT predicted WL over time and whether these effects were moderated by sex. Followup mediation analyses determined whether the effects of DT on WL could be explained by either changes in diet or PA. Results: Females reported higher DT as compared with males at baseline ( P < .001). We observed a significant sex × time × DT interaction on WL ( P < .04), such that higher DT predicted WL in males ( P < .04), but not in females ( P = .54). This effect of DT on WL in overweight and obese males was mediated by changes in PA (indirect effect, −0.43; 95% CI, −1.52 to −0.05), but not changes in energy intake. Conclusions: Among young adults with overweight and obesity who have higher DT, PA appears to be more important to WL than caloric restriction, particularly in males. Abstract : The desire to lose weight (ie, drive for thinness) is one psychological predictor of weight loss in adults with obesity. This study examined whether drive for thinness is associated with weight loss in adults with overweight and obesity and whether this weight loss is mediated by physical activity or diet.